Can Immigrant Employment Alleviate the Demographic Burden? The Role of Union Centralization - Alexander Kemnitz (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2006)
We examine how labor immigration affects public pensions under centralized wage setting. We show that immigration improves the sustainability of pay-as-you-go pensions if and only if total employment declines. This occurs if the labor demand elasticity exceeds the unemployment rate.
Keywords: J51; H55; F22; 330; Immigration; Public Pensions; Trade Union; Einwanderung; Internationale Arbeitsmobilität; Rentenfinanzierung; Gesetzliche Rentenversicherung; Lohnbildung; Gewerkschaftlicher Organisationsgrad; Theorie